Pengaruh Kemudahan, Manfaat Dan Pengetahuan Terhadap Minat Penggunaan E-Commerce Pada Generasi Z - Mahfiyah Mahfiyah; Muthmainnah Muthmainnah (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2023)
Abstract This study aims to determine the effect of convenience, benefits and knowledge on the interest in using e-commerce in generation Z. The method in this study uses descriptive quantitative methods. Data was taken by distributing the questionnaire link to Generation Z in Jember Regency as many as 138 people. Data were analyzed using the SPSS 2019 application with multiple linear regression analysis. The results of the analysis show that partially: Ease of Use has a significant positive effect on interest in using e-commerce in Generation Z. Usefulness/Benefits have a significant positive effect on interest in using e-commerce in Generation Z. Knowledge has a significant positive effect on interest in using e-commerce commerce in Generation Z. Simultaneously convenience, benefits and knowledge have a significant effect on the interest in using e-commerce in generation Z.